Calculating Ethics in the Fourteenth Century
1 online resource (368 pages)
Keywords: Calculating Ethics in the Fourteenth Century addresses a moment in the history of ethics, when discoveries in natural philosophy blurred the boundary between the possible and the impossible, and made the impossible a preferred territory in discussions on practical reason. The volume studies the onset and expansion of a new movement in constructing ethics, as the methods, arguments, and cases adopted from logic and natural philosophy came to be extensively applied at Oxford and swiftly disseminated among other Oxonians eventually making their way outside Oxford. It shows how the Oxford Calculators triggered a unique and durable transformation in ethics. Contributors are Pascale Bermon, Valeria Buffon, Michael W. Dunne, Marek Gensler, Simon Kemp, Edit A. LukÃ¡cs, Monika MichaÅ‚owska, and Andrea Nannini.